Materials for tissue engineering - Stevens, Molly; George, Julian (Henry Stewart Talks, 2007)
Range of materials considered for tissue engineering, Research into cell-material interaction, Development of new technologies, Highly tailored biomaterials: role in guiding cell behaviour and tissue regeneration, Medical implants, The use of commonly available clinical bioresorbable polymers, The use of bioactive materials: Bioglass, Utilising self-assembling nanoscale fibres, peptide functionalisation and recombinant DNA technology, Replication of structure and function of natural tissue, Importance of production techniques to control material macro and nano structure